Analysis of The Effect of Product, Price, Place, and Promotion on Spectator Loyalty of The Surabaya Football Kicking League - Muhammad Aldiansyah (Lavish Opulent Education, 2025)
This study aims to analyze the influence of Product (Event Experience), Price (Ticket Price & Participation Fee), Place (Location & Accessibility), and Promotion (Promotion & Digital Marketing) on Participant Loyalty in the 2025 Liga Tendang Bola Surabaya (LTB Surabaya 25). With the global sports industry projected to contribute 599.9 billion to global GDP by 2025, the importance of organizing effective local sports events has increased. This research employs a quantitative approach using multiple linear regression analysis, based on data collected from 370 Gen Z respondents who attended LTB Surabaya 25. The results indicate that all four variables have a positive and significant effect on participant loyalty, both partially and simultaneously. These findings are expected to serve as a basis for developing business strategies in local sports events to enhance participant loyalty and ensure the sustainability of future events.